Effects of Bacillus subtilis and Saccharomyces cerevisiae inoculation on soil bacterial community and rice yield under combined irrigation with reclaimed and fresh water - Lu, Hongfei; Qi, Xuebin; Li, Ping; Qiao, Dongmei; Rahman, Shafeeq ur; Bai, Fangfang; Cui, Jiaxin (International Journal of Agricultural and Biological Engineering, 2022)
In order to save fresh water and reduce soil salt accumulation, reclaimed water-fresh water combined irrigation, i.e, irrigation with reclaimed water for 50 d and then with fresh water till harvest, was used in rice planting. Bacillus subtilis and Saccharomyces cerevisiae were inoculated into the soil at the end of reclaimed water irrigation. The inoculation weight per pot of these microorganisms was as follows: 0 g and 0 g (J0), 5 g and 0 g (J1), 3.75 g and 1.25 g (J2), 2.5 g and 2.5 g (J3), 1.25 g and 3.75 g (J4), and 0 g and 5 g (J5), respectively. Treatment using reclaimed water in the whole stage was used as the control (CK). The plant height, tiller, physical and chemical properties of the soil, and soil bacterial diversity were measured. It was found that the plant height of rice was increased significantly by J1-J5 treatments. The dry weight of rice root, stem, and panicle and the 1000-grain weight increased significantly, while the leaf dry weight decreased. Microorganism inoculation significantly increased the nutrient absorption capacity of the crops. J1, J2, and J4 treatments significantly increased the amount of nitrate-nitrogen, ammonium nitrogen, available phosphorus, and available potassium, while J3, J4, and J5 treatments increased the soil organic matter, and microbial inoculation significantly decreased the EC of soil. J4 treatment induced the largest reduction in EC, and microorganisms treatments increased soil pH. Bacterial function prediction based on the KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway indicated that soil metabolic function was not significantly disturbed by the treatments. Organic matter and pH are the two main factors affecting the structure of the bacterial community in soil. 3.75 g of B. subtilis and 1.25 g of S. cerevisiae per pot is the best inoculation ratio.Keywords: Bacillus subtilis, Saccharomyces cerevisiae, rice, reclaimed water, soilDOI: 10.25165/j.ijabe.20221503.6423Citation: Lu H F, Qi X B, Li P, Qiao D M, Shafeeq-u-R, Bai F F, et al. Effects of Bacillus subtilis and Saccharomyces cerevisiae inoculation on soil bacterial community and rice yield under combined irrigation with reclaimed and fresh water. Int J Agric & Biol Eng, 2022; 15(3): 33–46.